Effect of Early Postoperative Resolution of MRI Signal Intensity Changes on the Outcomes of Degenerative Cervical Myelopathy. Issue 9 (1st May 2023) - Tozawa, Keiichiro; Nagata, Kosei; Ohtomo, Nozomu; Ito, Yusuke; Nakamoto, Hideki; Kato, So; Doi, Toru; Taniguchi, Yuki; Matsubayashi, Yoshitaka; Tanaka, Sakae; Oshima, Yasushi
Abstract : Study Design: A retrospective cohort study. Objective: To investigate whether the timing of postoperative resolution of increased signal intensity (ISI) in the spinal cord is associated with surgical outcomes. Summary of Background Data: It remains unclear whether changes in ISI in the early postoperative period influence surgical outcomes. Methods: This retrospective cohort study evaluated consecutive patients undergoing surgery for degenerative cervical myelopathy at a single academic hospital between January 2012 and September 2019. These patients underwent magnetic resonance imaging (MRI) preoperatively, within two weeks postoperatively (early MRI) and after six months postoperatively (late MRI). ISI was classified as follows: grade 0, none; grade 1, light (obscure); and grade 2, intense (bright). Patients were categorized into the following three groups: those with postoperative ISI resolution at early MRI (group E) or only at the late MRI (group L) stage and those whose ISI was persistent (group P). The surgical outcomes were compared between these three groups. Results: We included 204 patients with complete data eligible for the analysis, and 163 of them had preoperative ISI. Postoperative ISI regression was observed in 49 (30.1%) patients. Of these 49 patients, 25 showed ISI resolution at early MRI (group E) and 24 only at late MRI (group L). All 49 were grade 1 on preoperative MRI, and this was not found to significantly impact surgical outcomes. In comparing surgical outcomes between the groups, group E had better postoperative Japanese Orthopedic Association scores and Japanese Orthopedic Association recovery rates than groups L and P. No significant differences were observed between groups L and P. Conclusions: Early resolution of preoperative grade 1 ISI on postoperative T2-weighted MRI may be associated with better surgical outcomes in patients with degenerative cervical myelopathy undergoing cervical spinal surgery.